Reductive inactivation of digitoxin by Eubacterium lentum cultures. - Chandrasekaran, A (1987)
The obligate anaerobe Eubacterium lentum inactivated the cardiac glycoside digitoxin by reducing the double bond in the lactone ring. This conversion was quantitative when the substrate was incubated at a concentration of 10 micrograms/ml. The reduction reaction coincided with the growth phase of the bacterium. The stereochemical configuration at C-20 of the reduction product dihydrodigitoxin was found to be R. Incubation of digitoxigenin and its mono- and bisdigitoxosides individually with E. lentum led to the formation of their respective dihydro derivatives. The configuration at C-20 of these reduced metabolites was also found to be R.